Assessment of Over-The-Counter Medicine Sellers’ Knowledge in Artemisinin-Based Combination Therapy (Act) in Ho Municipal District, Volta Region, Ghana - Owusu-Mensah, F. (University of Ghana, 2023)
Malaria is a substantial public health concern associated with a high prevalence of sickness and mortality, especially among pregnant women and children below the age of five in Sub-Saharan Africa. In response to the worsening of the pandemic due to the ineffectiveness of single-drug treatments like chloroquine, the World Health Organization (WHO) promptly recommended the use of Artemisinin-combination therapies (ACTs) un 2001 (World Health Organization, 2020). In Ghana, private pharmaceutical retail businesses, namely Over-The-Counter (OTC) pharmacy shops, are the primary choice for treating malaria due to their simple accessibility and short waiting periods. However, the medication offered by Over-The-Counter (OTC) pharmaceutical stores often does not comply with the official criteria for Antimalarial drug treatment. Failure to comply with the prescribed measures might lead to the development of cerebral malaria and severe anemia. Hence, it is crucial to assess the expertise of over-the counter medication vendors (World Health Organisation, 2018). The main objective was to evaluate the level of knowledge among Over-The-Counter (OTC) pharmaceutical vendors about Artemisinin-Based Combination Therapies (ACTs) in the Ho Municipal District. The study used a descriptive cross-sectional methodology, using a pretested, reliable, and validated semi-structured questionnaire to assess the understanding of antimalarial treatment (ACT) among over-the-counter medicine (OTCM) sellers. The OTC medication vendors in the Ho municipal area made up the research population. The Pharmacy Council in the Volta Region has compiled a list of nearby over-the-counter (OTC) medicine retailers. The data was analyzed with STATA version 17. The statistical analysis was done correctly, and conclusions were drawn. The study results reveal that a significant majority of OTC drug sellers possess a strong understanding of ACTs, as shown by 81% displaying competency. However, to stop resistance from developing in the future, it's critical to educate over-the-counter drug dealers thoroughly about Artemisinin-based Combination Therapies (ACTs).
MPH.
Keywords: Over-The-Counter (OTC) pharmacy shops; Ho Municipal District; Malaria